Essays in economics of education: lessons from the 2010 earthquake in Chile - Pincheira Sarmiento, Bernardo Eugenio (2019)
This thesis comprises two research papers that use the 8.8 earthquake that struck Chile in 2010 as a source of exogenous variation in: peer composition for the first paper and in school year length in the second one. My first paper, chapter 2 of this thesis, studies the causal effect of classmates on students’ academic performance, known as peer effects. I use the earthquake as a source of variation in peer composition, using the fact that the earthquake hit a random area of the country and forced some students to move into new schools for non-academic reasons. I use OLS and instrumental variables econometric specifications, with data from students observed in 2010, in affected or non-affected areas, to answer this question. The regressions are performed only on students who do not move, the stayers. My results show that the peer effects are positive for students in both fourth and tenth grade, but statistical significance is sensitive to the specification chosen when using instrumental variables. An increase of one standard deviation in the average score of the peers has an effect between 0.15 and 0.22 standard deviations in the student's own score. In addition, using IV quantile regressions, I find some evidence of nonlinearities in the effect. The nonlinearities are not strong enough to allow me to find a pareto improving allocation of students, but it potentially allows for a certain allocation of students within school that might reduce educational inequality between students and marginally increase average performance according to simulations. The second paper, chapter 3 of this thesis, studies the causal effect of school year length on students' academic performance. I use a difference-in-differences econometric specification, with data from students in fourth grade of primary education observed in 2009 or 2010, to answer this question. I rely on the earthquake that happened in Chile in 2010 as the source of variation. More than 50% of the students were studying in schools located in the area affected by the earthquake. The main results show that students attending schools that closed for up to eight weeks decreased their academic performance compared to the control group of students in non-affected areas. The effect is statistically significant only in mathematics. On average students exposed to up to 5% less of time at school have a performance of nearly 0.08 standard deviations lower than the counterfactual group of students in non-affected areas in mathematics. Of this effect, only one half can be attributed to having fewer days of schooling.